Determinan Sosial Pasien Tuberkulosis Sebagai Faktor Resiko Penularan Tuberkulosis Riwayat Kontak Serumah di Wilayah Kerja Puskesmas Panjang dan Sukaraja - Annas Fadhillah Bilqishti; Dyah Wulan Sumekar; T.A. Larasati (CV. Jasa Sukses Abadi, 2020)
Pulmonary tuberculosis (TB) is transmitted through droplets. The possibility of TB infection is greater in groups close to patient, especially at home. Risk factors that influence TB are social determinants in the form of education level, employment, income and social class; The purpose of this study was to determine the effect of social determinants as risk factors for pulmonary TB transmission with a history of household contact. This research uses Case Control method. Case population was taken from smear TB patients (+) in July-December. Case and control samples were taken by respondents amounted of 30 people. Data analysis was performed by Chi Square test. Results The proportion of respondents from the case sample (53%) was male. For the control sample it was found (76%) that was also male. There was no relationship between education and household contact with TB (P = 0.605) work (P = 0.605), income ((P = 0.193), nor social class (0.111). Risk factors for household contact TB: Social determinants are not a risk factor for transmission of household contact tuberculosis